Eco-theology Movements from India: Trajectories, Challenges, and Promises - Zachariah, George (Indonesian Journal of Theology, 2025)
India has a long and diverse history of eco-theological thinking and praxis, and this essay attempts to identify and study those diverse trajectories of Indian eco-theologies. The essay further engages with different ecological philosophies and eco-justice movements from India and examines their impact on the politics of the Indian eco-theology movements. The essay concludes with a critical interrogation of the mainstream eco-theology movement in India and a re-vision of eco-theological imaginations and praxis, informed by subaltern and Indigenous perspectives.